Rolling out defects during rolling of castings at the mill 850 of Belarussian metallurgical plant - V. I. Scherbakov; V. V. Filippov; V. A. Tischenko; M. I. Titov (Литьë и металлургия)
Results of industrial experiment are given and regularities of rolling out of surface defects of artificial origin are investigated at rolling of continuous castings at the rolling mill 850 of Belarussian metallurgical plant